Effect of Thickness on Fluorescence of Some Clinical Dental Ceramics - Sedighe Sadat Hashemikamangar; Sara Valizade; Alireza Mahmoudi Nahavandi; Masoomeh Hasani Tabatabaei; Marzieh Daryadar (Tehran University of Medical Sciences, 2021)
Objectives: This study aimed to develop a new method for measurement of florescence and compare the fluorescence of some clinical dental ceramics in different thicknesses. Materials and Methods: Forty-eight samples of feldspathic (Vita VM9, A2), IPS e.max (Ivoclar HT, A2), zirconia (Korox Zircostar, A2) and Enamic (Vita A2) ceramics were used in this study in 0.5 and 1 mm thicknesses. The fluorescence of the samples was measured by using a developed technique. The results were analyzed by two-way ANOVA and Duncan post-hoc test. P<0.05 was considered significant. Results: Enamic, feldspathic and e.max ceramics had significantly different fluorescence in descending order (P=0.000). Fluorescence of ceramics increased with an increase in their thickness from 0.5 to 1 mm (P=0.007). Conclusion: The results confirmed the applicability of the presented method for measurement of fluorescence of dental ceramics. While, the thickness of restoration determines the concentration of the fluorescent agent, some additional technical information is required for justification of the observed trend in the studied ceramics. Keywords: Fluorescence; Ceramics; Zirconium Oxide; VITA Enamic